2004
DOI: 10.1161/01.str.0000147045.71923.18
|View full text |Cite
|
Sign up to set email alerts
|

Do Normal D-dimer Levels Reliably Exclude Cerebral Sinus Thrombosis?

Abstract: Background and Purpose-Cerebral sinus thrombosis (CST) needs to be considered in the differential diagnosis of all patients with acute headache. Early diagnosis is essential because early treatment may prevent morbidity and may even be life-saving. Definite exclusion, however, needs advanced neuroradiologic diagnostics, which are not readily available in many hospitals. Because measurement of D-dimers has been demonstrated to be helpful in excluding thromboembolic disease, our aim was to investigate whether D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
3
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 19 publications
4
42
3
8
Order By: Relevance
“…In a well-designed prospective, multicenter study of 343 patients presenting to the emergency department with symptoms that suggested CVT, a positive D-dimer level (defined as a level Ͼ500 g/L) was found in 34 of 35 patients with confirmed CVT and 27 of 308 patients without CVT. 82 This yielded a sensitivity of 97.1%, a specificity of 91.2%, a negative predictive value of 99.6%, and a positive predictive value of 55.7%, which supports a clinically useful role of D-dimer in excluding CVT. A normal D-dimer level according to a sensitive immunoassay or rapid ELISA may help identify patients with a low probability of CVT.…”
Section: D-dimersupporting
confidence: 58%
See 1 more Smart Citation
“…In a well-designed prospective, multicenter study of 343 patients presenting to the emergency department with symptoms that suggested CVT, a positive D-dimer level (defined as a level Ͼ500 g/L) was found in 34 of 35 patients with confirmed CVT and 27 of 308 patients without CVT. 82 This yielded a sensitivity of 97.1%, a specificity of 91.2%, a negative predictive value of 99.6%, and a positive predictive value of 55.7%, which supports a clinically useful role of D-dimer in excluding CVT. A normal D-dimer level according to a sensitive immunoassay or rapid ELISA may help identify patients with a low probability of CVT.…”
Section: D-dimersupporting
confidence: 58%
“…A normal D-dimer level according to a sensitive immunoassay or rapid ELISA may help identify patients with a low probability of CVT. 82,83 A subsequent study of 73 patients with confirmed CVT found normal D-dimer levels in 7 patients (10%). 83 Five of the 7 patients with confirmed CVT and negative D-dimer presented with isolated headache, which suggests that this subgroup might be particularly at risk of false-negative results of D-dimer testing.…”
Section: D-dimermentioning
confidence: 96%
“…5,9,10 In a study of 239 patients with suspected cerebral venous thrombosis, D-dimer testing was performed in 98 patients. 5 D-dimer testing was associated with a 9% false-positive rate and a 24% false-negative rate.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…A multicenter prospective study examined d-dimer sensitivity in the evaluation of CVT in which 35 patients were diagnosed with CVT and 34 had a positive d-dimer. When comparing to 308 patients without CVT, 27 had positive d-dimers, yielding a sensitivity of 97.1%, specificity of 91.2%, negative predictive value of 99.6%, and positive predictive value of 55.7% [32]. Negative d-dimer levels can help rule out CVT in patients with low suspicion for the diagnosis [23].…”
Section: Other Diagnostic Testsmentioning
confidence: 98%